Eksplorasi Target Pasar dan Strategi Pemasaran Home Industri Sandal Teplek di Ciomas, Bogor - Sofia Maqom Al Mahmudah; Sukemi Sukemi; Suniyati Suniyati; Siti Mariah; Sobirin Sobirin (Universitas Nusantara PGRI Kediri, 2026)
This study aims to determine the characteristics and behavior of the target market and the marketing strategies implemented by the home industry of flat sandals in Ciomas, Bogor. The research method used was qualitative, with data collection techniques through direct interviews with flat sandal producers. The results show that this home industry has been established since 1992 and produces sandals that are popular with various groups, from teenagers to adults. Consumers choose these products for their comfort, diverse designs, and affordable prices. The marketing strategy implemented is still traditional, namely through direct sales and collaboration with partner stores. However, product quality is a key factor in retaining existing customers and attracting new buyers. The obstacle faced by producers is limited customer data, so market analysis cannot be carried out optimally. This study recommends that producers begin implementing digital marketing strategies and recording consumer data to expand market reach and increase business competitiveness in the future.